Retinopathy of Prematurity : Current Diagnosis and Management - Kychenthal B., Andrés; Dorta S., Paola (Springer International Publishing : Imprint: Springer, 2017)
This clinically oriented book is devoted to the diagnosis and treatment of retinopathy of prematurity (ROP), a leading cause of childhood blindness. World-renowned experts in the field discuss epidemiologic and pathogenic aspects of the disease. The staging and classification of ROP are explained in detail, and guidance is provided on appropriate anesthesia. The state of the art in imaging of ROP is described and illustrated, with coverage of the advances in ophthalmic imaging technology and telemedicine that have revolutionized pediatric retinal examinations and contributed significantly in elucidating the pathophysiology of ROP and improving diagnosis and treatment. Treatment indications and therapeutic alternatives, including the use of antiproliferative drugs, are addressed in separate chapters, supplying the reader with the most up-to-date knowledge in the field.
Keywords: Medicine.; Obstetrics.; Ophthalmology.; Pediatrics.; elektronické knihy; electronic books